Drying kinetic models, thermodynamics, physicochemical qualities, and bioactive compounds of avocado (Persea americana Mill. Hass variety) seeds dried using various drying methods - Desta Dugassa Fufa; Tilahun Bekele; Aynadis Tamene; Geremew Bultosa (Heliyon)
Avocados are among the most well-known nutrient-rich fruits worldwide. However, there is a high production of by-product waste, mainly avocado seeds. Avocado seeds can be used in many functional food and non-food applications, due to their nutritional and health-promoting properties. However, preservation technologies such as drying are essential to increase shelf life and preserve bioactive compounds. It has been anticipated that pre-drying techniques could improve the quality of dried products. This study investigates the drying kinetics of avocado seed slices that have been subjected to different pre-treatments (ascorbic acid, blanching, roasting) and drying methods (fluidized bed dryer, hot air dryer, and solar dryer) using freeze-dried samples as a control. In addition, the interaction effect of pretreatment and drying methods on the thermodynamic properties, physicochemical quality, and bioactive compounds of dried avocado seeds were also evaluated. Results indicate that the logarithmic model provides the best fit for the experimental data on drying kinetics. Thermal profile coefficients for avocado seeds activation energy and effective moisture diffusivity were predicted to range from 80.91 to 97.02 kJmol-1, and 4.8 to 5.8 × 10−10 m2s−1, respectively. Moreover, the study showed that the sample treated with roasting and dried using hot air drying (HAD) achieved the maximum desirability value of 0.9256 for thermal profile coefficients. In terms of nutritional and bioactive compound retention, samples treated with ascorbic acid and dried using a fluidized bed dryer (FBD) exhibited maximum values of phenols (106.6 mg GAE/100 g) and vitamin C (77 %), along with a total colour difference recovery of 86 %. In summary, dried avocado seeds are a valuable source of macronutrients and bioactive compounds, highlighting their potential as functional ingredients in the food industry. Furthermore, the implications of this research finding is to produce stable products with better quality from plant by-products using the proper drying methods and promoting a circular economy.